PENGARUH PUPUK KANDANG KAMBING DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG TANAH (Arachis hypogea L) - Suryanto, Suryanto (Fakultas Pertanian, Universitas Janabadra, 2022)
This research was conducted in the Experimental Garden of Muhammadiyah University of South Tapanuli, the purpose of this study was to determine the effect of goat manure and plant spacing on the growth and production of long beans. The design used was factorial 4 x 3 in a randomized block design (RBD) with 3 replications. The first factor is the dose of goat manure with 4 stages, namely: K0 = 0, K1 = 0.5 kg/plot, K2 = 1 kg/plot, K3 = 2 kg/plot. The second factor is spacing with 3 stages, namely: J1 20cm x 20cm, J2 30cm x 20cm and J3 40cm x 20cm. From the results of the study based on statistical analysis of the parameters of plant height, flowering age, pod weight per sample and pod weight per plot on goat manure treatment, plant spacing and interaction of goat manure, plant spacing had a significant effect. The parameter of plant height for giving goat manure at the treatment dose of 2 kg/plot was 65.44 cm, the spacing treatment was 20 cm x 20 cm, namely 58.33 cm and the highest interaction of goat manure and plant spacing was found at the dose of goat manure at a dose of 2 kg/ plots and with a spacing of 20 cm x 20 cm which is 72.33 cm, the flowering age parameter where in the goat manure treatment there is the fastest flowering age results are found in the treatment with a dose of 0.5 Kg/plot which is 38.11 days, the fastest spacing treatment is 20 cm x 20 cm is 38.50 and the interaction of goat manure and spacing, the fastest flowering age is found in goat manure at a dose of 0.5 kg/plot and with a spacing of 20 cm x 30 cm, which is 37 days, on the persapel pod weight parameter at the goat manure treatment had the highest yield at the treatment dose of 2 Kg/plot, namely 149 gr, the spacing treatment was 40 cm x 20 cm, namely 135.91 gr and the highest interaction of goat manure and plant spacing was found at the goat manure dose of 2 kg/plot and with a spacing of 40 cm x 20 cm which is 159 gr, in the treatment of pod weight per plot in the goat manure treatment there is the highest yield in the treatment of a dose of 2 Kg/plot which is 3440 gr, the spacing treatment is 40 cm x 20 cm which is 2850 gr and fertilizer interactions goat shed and the highest spacing was found at the dose of goat manure at a dose of 2kg/plot and with a spacing of 40 cm x 20 cm, namely 3750 gr.INTISARIPenelitian ini telah dilaksanakan di kebun percobahan Universitas Muhammadiyah Tapanuli Selatan, , tujuan penelitian ini adalah untuk mengetahui pengaruh pupuk kandang kambing dan jarak tanam terhadap pertumbuhan dan produksi kacang panjang. Rancangan yang digunakan adalah faktorial 4 x 3 dalam rancangan acak kelompok (RAK) dengan 3 ulangan. Faktor pertama dosis pupuk kandang kambing dengan 4 tarap yaitu : K0 =0 , K1 = 0,5Kg/plot, K2 = 1 Kg/plot, K3 = 2Kg/plot. Faktor kedua Jarak tanam dengan 3 tarap yaitu : J1 20cm x 20cm, J2 30cm x 20cm dan J3 40cm x 20cm. Dari hasil penelitian berdasarkan analisis secara statistik parameter tinggi tanaman, umur berbunga, berat berat polong persampel dan berat polong per plot terhadap perlakuan pupuk kandang kambing, jarak tanam dan interaksi pupuk kandang kambing, jarak tanam berpengaruh nyata. Parameter tinggi tanaman pemberian pupuk kandang kambing pada perlakuan dosis 2 Kg/plot yaitu 65,44cm, perlakuan jarak adalah 20 cm x 20 cm yaitu 58,33 cm dan interaksi pupuk kandang kambing dan jarak tanam tertinggi terdapat pada dosis pupuk kandang kambing dosis 2kg/plot dan dengan jarak tanam 20 cm x 20 cm yaitu 72,33 cm, parameter umur berbunga dimana pada perlakuan pupuk kambing terdapat hasil umur berbunga tercepat terdapat pada perlakuan dosis 0,5 Kg/plot yaitu 38,11 hari, , perlakuan jarak tercepat adalah 20 cm x 20 cm yaitu 38,50 dan interaksi pupuk kandang kambing dan jarak tanam umur tercepat berbunga terdapat pada pupuk kandang kambing dosis 0,5kg/plot dan dengan jarak tanam 20 cm x 30 cm yaitu 37 hari, pada parameter berat polong persapel pada perlakuan pupuk kambing terdapat hasil tertinggi pada perlakuan dosis 2 Kg/plot yaitu 149 gr, perlakuan jarak adalah 40 cm x 20 cm yaitu 135,91 gr dan interaksi pupuk kandang kambing dan jarak tanam tertinggi terdapat pada dosis pupuk kandang kambing dosis 2kg/plot dan dengan jarak tanam 40 cm x 20 cm yaitu 159 gr, pada perlakuan berat polong per Plot pada perlakuan pupuk kambing terdapat hasil tertinggi pada perlakuan dosis 2 Kg/plot yaitu 3440 gr, perlakuan jarak adalah 40 cm x 20 cm yaitu 2850 gr dan interaksi pupuk kandang kambing dan jarak tanam tertinggi terdapat pada dosis pupuk kandang kambing dosis 2kg/plot dan dengan jarak tanam 40 cm x 20 cm yaitu 3750 gr.